CUPPING THERAPY IN REDUCING BLOOD PRESSURE IN PATIENTS WITH HYPERTENSION: A LITERATURE STUDY - Ade Andrian, Ade Andrian (Asian Australasian Neuro and Health Science Journal (AANHS-J), 2023)
Introduction: The World Health Organization (WHO 2022) states that the current global prevalence of hypertension is 22% of the world's total population, and less than one-fifth make an effort to control their blood pressure, I assume. In Indonesia it is estimated at 15 million, but only 4% are under control. Hypertension can be caused by lifestyle, obesity, alcohol, smoking, stress, age, and genetic factors. Hypertension can be treated nonpharmacologically, namely with cupping therapy. This study aims to determine the effect of cupping therapy on lowering blood pressure in patients with hypertension. Method: using a literature review research design. International and national journal searches were obtained through several sources including: Proquest, ScienceDirect, Emerald Insight, Ebsco, and Google Scholar. There are 10 articles obtained that will be reviewed, the results of information about the application of complementary alternative therapy, namely cupping therapy, and analyzing the published literature so as to reduce blood pressure in hypertensive patients. Results: The results of the literature review indicate the effect of cupping therapy between before and after cupping therapy on changes in blood pressure in patients with hypertension. Conclusion: The provision of cupping therapy as a complementary alternative therapy or one of the non-pharmacological therapies greatly provides an effect in lowering blood pressure in patients with hypertension. Keywords: Blood Pressure, Cupping Therapy, Hypertension